The effects of warmed intravenous fluids, combined warming (warmed intravenous fluids with humid-warm oxygen), and pethidine on the severity of shivering in general anesthesia patients in the recovery room - Ahmad Nasiri; Ayob Akbari; GholamReza Sharifzade; Pooya Derakhshan (Wolters Kluwer Medknow Publications, 2015)
Background: Shivering is a common complication of general and epidural anesthesia. Warming methods and many drugs are used for control of shivering in the recovery room. The present study is a randomized clinical trial aimed to investigate the effects of two interventions in comparison with pethidine which is the routine treatment on shivering in patients undergoing abdominal surgery with general anesthesia. Materials and Methods: Eighty-seven patients undergoing abdominal surgery by general anesthesia were randomly assigned to three groups (two intervention groups in comparison with pethidine as routine). Patients in warmed intravenous fluids group received pre-warmed Ringer serum (38°C), patients in combined warming group received pre-warmed Ringer serum (38°C) accompanied by humid-warm oxygen, and patients in pethidine group received intravenous pethidine routinely. The elapsed time of shivering and some hemodynamic parameters of the participants were assessed for 20 min postoperatively in the recovery room. Then the collected data were analyzed by software SPSS (v. 16) with the significance level being P < 0.05. Results: The mean of elapsed time in the warmed intravenous serum group, the combined warming group, and the pethidine group were 7 (1.5) min, 6 (1.5) min, and 2.8 (0.7) min, respectively, which was statistically significant (P < 0.05). The body temperatures in both combined warming and pethidine groups were increased significantly (P < 0.05). Conclusions: Combined warming can be effective in controlling postoperative shivering and body temperature increase.